Physiological responses, hitting accuracy and step count of a tennis drill in function of court surface: a randomised cross-over design - Chapelle, L.; Clarys, P.; Meulemans, S.; Aerenhouts, D. (International Journal of Performance Analysis in Sport, 2017)
The present study examined physiological responses, hitting accuracy and step count during a tennis drill on both clay and hard courts. Twenty elite tennis players performed two identical ball machine led drills. Maximum and mean heart rate, energy expenditure, playing intensity (MET values) and step count were measured using the Polar RCX-5 device and the SenseWear Pro3 Armband. Hitting accuracy was calculated as the percentage of balls that were hit within marked zones. There was no significant difference and a trivial effect size between clay and hard court for maximal and mean heart rate, MET values and hitting accuracy. There was a small effect size and a trend towards a significantly higher energy expenditure on clay court. Step count showed a large effect size and was significantly lower on clay court. The correlations between step count, hitting accuracy and the physiological responses indicated little difference between clay and hard court. There was a significant moderate positive correlation between step count and hitting accuracy on hard court only. Despite a significant difference in step count, this study did not find a significant difference in physiological responses and hitting accuracy between clay and hard court during a ball machine led drill.